One stone for two birds: Endophytic fungi promote maize seedlings growth and negatively impact the life history parameters of the fall armyworm, Spodoptera frugiperda - Kinyungu, Sharon W.; Agbessenou, Ayaovi; Subramanian, Sevgan; Khamis, Fathiya M.; Akutse, Komivi S. (Frontiers in Physiology, 2023)
The fall armyworm (FAW) Spodoptera frugiperda, is a voracious pest of cereals native to the Americas and which invaded Africa in 2016. Chemical control is the main management option, which however remains ineffective and unsustainable. Fungal endophytes are increasingly used as alternative for the management of insect pests of economic importance. This study assessed the potential of eight endophytic fungal isolates to colonize maize plant and their ability to promote seedlings growth through seed and foliar inoculations, as well as their suppressive effects on FAW. Fungal colonization rates of different plant parts by the endophytes varied as per the inoculation methods. Beauveria bassiana ICIPE 279 colonized more than 60% of all the seedling parts while B. bassiana G1LU3 only colonized stem (25%) and leaf (5%) tissues through foliar inoculation. Trichoderma atroviride F2S21, T. asperellum M2RT4, T. harzianum F2R41, Trichoderma sp. F2L41, Hypocrea lixii F3ST1 and Fusarium proliferatum F2S51 successfully colonized all the plant parts and therefore were selected and further evaluated through seed inoculation for their endophytic persistence, effect on plant growth, and pathogenicity to Spodoptera frugiperda immature and adult stages. Weekly assessment showed varied effect of the endophytes on maize plant growth parameters compared to the control. During the first week, percentage colonization of the plant parts ranges between 90%–100%, 65%–100%, and 60%–100%, in the roots, stems, and leaves, respectively for all the five tested isolates. However, the colonization pattern/rates significantly decreased over time for H. lixii F3ST1 in the stems and leaves, and for T. harzianum F2R41 in the leaves and for T. asperellum M2RT4 in the roots. In addition, T. harzianum F2R41 outperformed all the other isolates in boosting the plant height, whereas H. lixii F3ST1 and T. asperellum M2RT4 outperformed all the other isolates in increasing the wet and dry shoots weight. Furthermore, the number of egg masses laid on endophytically-colonized maize plants varied among the treatments. Trichoderma asperellum M2RT4 and H. lixii F3ST1 endophytically-colonized maize plants significantly reduced the number of egg masses and the defoliation/feeding rates of the pest compared to the control. Additionally, T. harzianum F2R41 had the highest negative impact on the pupation and adult emergence of S. frugiperda with a female-biased sex ratio. Our findings indicate that T. asperellum M2RT4, T. harzianum F2R41, and H. lixii F3ST1 hold a potential to be developed as endophytic-fungal-based biopesticides for sustainable management of S. frugiperda and as plant growth promoters.